Asymmetrical phase-shifting carrier pulse-width modulation for harmonics suppression in cascaded multilevel converter under unbalanced DC-link voltages - Li, Shangsheng; Yang, Zezhou; Li, Qionglin; Gong, Jinwu; Sun, Jianjun; Zha, Xiaoming (2015 IEEE Energy Conversion Congress and Exposition (ECCE), 2015)
In a hybrid cascaded multilevel converter subject to different DC-link voltage levels among cascaded cells, should conventional carrier phase-shifting pulse-width modulation be applied, it will fail to multiply the equivalent switching frequency of the overall output voltage. As a consequence, this makes it more difficult to design the output filter and limits the overall output bandwidth. Based on the mathematical analysis of the switching harmonics in the overall output voltage, three possible strategies of switching harmonics suppression are proposed and discussed. A general asymmetrical carrier phase-shifting PWM for an n-cell-structure is then derived as the most effective strategy to eliminate switching harmonics. Also, its maximum capacity of harmonic suppression is given. Moreover, the engineering implementation of asymmetrical carrier phase-shifting PWM is presented. Simulation and experiment results verify the validity of the proposed asymmetrical carrier phase-shifting PWM.